2019
DOI: 10.1021/acsaem.8b02157
|View full text |Cite
|
Sign up to set email alerts
|

First-Principles Molecular Dynamics Simulations of UCln–NaCl (n = 3, 4) Molten Salts

Abstract: Molten chloride salts are one of the two main choices to dissolve nuclear fuels for fast-spectrum molten-salt reactors, as a generation IV reactor design. Both U3+ and U4+ can stably exist in molten chlorides, but the differences in their structure and chemical properties in molten NaCl are not well understood. In this work we use first-principles molecular dynamics simulations based on density functional theory to investigate the structure of UCl n (n = 3, 4) in molten NaCl at various mole fractions. We find… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
2
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(41 citation statements)
references
References 42 publications
2
31
2
2
Order By: Relevance
“…One interesting finding in our previous study [14] is the formation of U−Cl network structures, U m Cl x oligomers (m=2–4) and polymers (m>4), in the 1 : 1 NaCl−UCl n (n=3,4) molten salts. Figure 6a shows the change in the network structure from adding different amounts of MgCl 2 into NaCl−UCl 3 .…”
Section: Resultsmentioning
confidence: 81%
See 1 more Smart Citation
“…One interesting finding in our previous study [14] is the formation of U−Cl network structures, U m Cl x oligomers (m=2–4) and polymers (m>4), in the 1 : 1 NaCl−UCl n (n=3,4) molten salts. Figure 6a shows the change in the network structure from adding different amounts of MgCl 2 into NaCl−UCl 3 .…”
Section: Resultsmentioning
confidence: 81%
“…[8][9][10][11][12] NaCl is the main salt of choice to dissolve the fuel salt such as UCl 3 for fast-spectrum MSRs. [13] We have previously investigated the structural change and transport properties of the melts of NaCl with uranium chlorides using both first principles molecular dynamics [14] and classical molecular dynamics based on the polarizable-ion model. [15] Our studies revealed that the viscosity of the NaClÀ UCl 3 mixture increases with the uranium concentration as the network structure of UÀ ClÀ U is formed.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, let us compare the octahedra formed in molten NaCl–CrCl 3 and NaCl–UCl 3 (78 mol % NaCl). In the uranium salt, the most likely distance between U 3+ and Cl – is 2.74 Å . This is larger than the Cr–Cl distance of 2.342 Å, as dictated by the larger Shannon radius of U 3+ (1.025 Å for U 3+ vs 0.615 Å for Cr 3+ ) .…”
Section: Discussionmentioning
confidence: 92%
“…We also found evidence for a mid-range order that is likely related to interchain correlations. Therefore, our model ternary salt shows the structure that is reminiscent of NaCl−UCl n , 35 the salt that is likely to be used in MSRs. We expect that Cr impurities will affect network formation of the abovementioned salts, thus affecting the diffusivity and viscosity, especially near salt−metal interfaces.…”
Section: Experimental and Computational Resultsmentioning
confidence: 99%
“…We also found evidence for mid-range order that is likely related to inter-chain correlations. Therefore, our model ternary salt shows the structure that is reminiscent of KCl-MgCl 2 17 , LiF-BeF 2 18 , and NaCl-UCl n 19 , the salts that are likely to be used in MSRs. We expect that Cr impurities will affect network formation of the above-mentioned salts, thus affecting the diffusivity and viscosity, especially near salt-metal interfaces.…”
Section: Experimental and Computational Resultsmentioning
confidence: 99%